Carbon stocks and fluxes in tropical lowland dipterocarp rainforests in Sabah, Malaysian Borneo. - Philippe Saner; Yen Yee Loh; Robert C Ong; Andy Hector (PLoS ONE, 2012)
Deforestation in the tropics is an important source of carbon C release to the atmosphere. To provide a sound scientific base for efforts taken to reduce emissions from deforestation and degradation (REDD+) good estimates of C stocks and fluxes are important. We present components of the C balance for selectively logged lowland tropical dipterocarp rainforest in the Malua Forest Reserve of Sabah, Malaysian Borneo. Total organic C in this area was 167.9 Mg C ha⁻¹±3.8 (SD), including: Total aboveground (TAGC: 55%; 91.9 Mg C ha⁻¹±2.9 SEM) and belowground carbon in trees (TBGC: 10%; 16.5 Mg C ha⁻¹±0.5 SEM), deadwood (8%; 13.2 Mg C ha⁻¹±3.5 SEM) and soil organic matter (SOM: 24%; 39.6 Mg C ha⁻¹±0.9 SEM), understory vegetation (3%; 5.1 Mg C ha⁻¹±1.7 SEM), standing litter (<1%; 0.7 Mg C ha⁻¹±0.1 SEM) and fine root biomass (<1%; 0.9 Mg C ha⁻¹±0.1 SEM). Fluxes included litterfall, a proxy for leaf net primary productivity (4.9 Mg C ha⁻¹ yr⁻¹±0.1 SEM), and soil respiration, a measure for heterotrophic ecosystem respiration (28.6 Mg C ha⁻¹ yr⁻¹±1.2 SEM). The missing estimates necessary to close the C balance are wood net primary productivity and autotrophic respiration.Twenty-two years after logging TAGC stocks were 28% lower compared to unlogged forest (128 Mg C ha⁻¹±13.4 SEM); a combined weighted average mean reduction due to selective logging of -57.8 Mg C ha⁻¹ (with 95% CI -75.5 to -40.2). Based on the findings we conclude that selective logging decreased the dipterocarp stock by 55-66%. Silvicultural treatments may have the potential to accelerate the recovery of dipterocarp C stocks to pre-logging levels.